(untitled) (Research, Society and Development, 2022)
The world population is experiencing a pandemic caused by the coronavirus, also called COVID-19 or SARS-Cov-2. This disease presents a clinical picture that varies from asymptomatic infections to severe conditions, and can also be confused with a cold. In Brazil, the first case of the disease was notified on February 25, 2020 and the number of people affected by the virus has been growing gradually since then. This is a cross-sectional, descriptive, analytical and quantitative study, whose data collection will take place between July 2021 and August 2021, where it was carried out in Teresina-PI. The sample for the present study was dimensioned in 84 participants considering a population of 10,903 commercial workers registered in SINDCOM, in Teresina. The data collection instruments will be the questionnaires (SRQ 20 – Self Report Questionnaire), DASS – 21, DAST-20 and the User Identification and Working Conditions. The results obtained in the questionnaires applied showed that 30.12% of the study population has mental suffering and 69.88 does not have criteria to demonstrate that they have mental suffering. The analysis of the answers given by the participants to the questions of a sociodemographic nature by the Chi-square test, showed, for the most part, independence from the results obtained in the assessment of mental suffering by the SRQ-20, that is, the answers given to these questions were not significantly different (p>0.05) in people with mental distress measured by the SRQ-20 than in those without mental distress.